(untitled) (The Review of Diabetic Studies, 2024)
Background: Oral diseases remain among the most prevalent non-communicable conditions globally and are increasingly recognized as integral to systemic health. Fragmentation between dental services and broader healthcare systems continues to limit diagnostic accuracy, treatment safety, and continuity of care. Objective: To present a comprehensive multidisciplinary oral healthcare framework that integrates Health Information Management, Dental Practice, Laboratory Diagnostics, and Pharmacotherapy, highlighting the distinct and complementary roles of each specialty from diagnosis to treatment. Methods: This narrative review synthesizes evidence from dental medicine, health informatics, laboratory science, and pharmacology literature to construct an integrated care model emphasizing clinical coordination, data interoperability, and evidence-based decision-making. Results: Health Information Management enables continuity, risk stratification, and clinical decision support; dental practice functions as the diagnostic and therapeutic core; laboratory diagnostics enhance precision through biomarker analysis and histopathology; and pharmacotherapy ensures safe, effective, and individualized treatment. When integrated, these domains improve diagnostic accuracy, patient safety, therapeutic outcomes, and system efficiency. Conclusion: A multidisciplinary, information-driven oral healthcare framework is essential for modern practice. Effective integration across specialties strengthens patient-centered care, reduces clinical risk, and aligns oral health with broader healthcare objectives.